The Royal Observatory Greenwich A Glance at its History and Work - Maunder, E. Walter 1851-1928 (Cambridge University Press, 1900)
When this highly illustrated work first appeared in 1900, the day-to-day business of an astronomer was prone to misapprehension; the reality tended to be clouded by the temptation to imagine observatories as preoccupied with making awe-inspiring discoveries and glimpsing distant worlds. Describing himself as a hybrid between an engineer and an accountant, astronomer Edward Walter Maunder (1851-1928) explodes the romantic myths and takes the reader on an entertaining tour of the history and real purposes of the Royal Observatory at Greenwich. Founded with the sole aim of advancing navigation at sea, the observatory originally confined its activities to the accurate compilation of celestial charts. In exploring the observatory's various departments and the lives of its Astronomers Royal, Maunder shows how its remit slowly expanded into heliography, meteorology, spectroscopy and the study of magnetism, which transformed it from a tool of the Navy to a major institution in contemporary astronomy.
Keywords: Royal Observatory, Greenwich -- History.